Without morals in a moral world—the expanding moral circle of The Witcher 3: The Wild Hunt - Johansson, Magnus; Rübsamen, Michael (Frontiers in Communication, 2024)
As video and computer games get increasingly more advanced, the immersive experience for the player also follows this trajectory. One aspect that has been explored to great lengths in these games is that of choice and player agency. Often these choices and acts are of moral character, whether it be choosing what to do on an ambiguously formulated questline with multiple branches, or how to approach different creatures within the game world. The game The Witcher 3: The Wild Hunt is used as a case of a game that makes use of many mechanisms related to moral issues and morality. Through a critical reading of the game this article explores the ways in which players are faced with the game's moral order. Utilizing Singer's idea of the expanding moral circle the article explores the game world's establishing of moral issues, including who and what are actually included in the expanding circle, and in what way this is conveyed within the game. Relying on the dual nature of gameplay, where players are role-playing as the witcher Geralt of Rivia as well as experiencing what unfolds in the game in front of a screen, the article argues that these moral orders, the one in the game world and the one in "real" life, are to be included in analysis to fully understand the moral underpinnings of a digital game. The article also uses the case of encountering non-human animals as a further illustrative case, where the player is often only left with very few choices in which to act, which are not presented as moral in-game. Furthermore, the article argues for a further development of the theoretical framework as a possible vantage point from where to understand morality and how they emanate in different game worlds.